Professionally Significant Qualities Upbringing at the Engineering Education System - D. P. Danilaev; N. N. Malivanov (Высшее образование в России)
The future engineers training system should include a special target function of professionally significant qualities developing, which are necessary along with professional competencies, both for work in the chosen field of activity and for further career growth. The professional education often turns out to be formal, and the training of engineers is not effective enough, without clear goals.The purposes of the article are the importance substantiate of the future engineers professional upbringing, to identify the organization problems at the professionally significant qualities formation and to determine their resolution conditions for the engineering education system. The work examines research questions: what does professional upbringing to engineering education contribute, what professionally significant qualities complement the knowledge component in the competencies of future engineers.Materials and methods. The article provides an overview of scientific research and the state of the professional upbringing of future engineers issue. The theoretical basis of the study is the decomposition and isolation of the engineering education system important component – the education of professionally significant qualities with its special meaning and functionality.Results and conclusions. Discipline, responsibility, independence and self-organization can be considered as professionally significant personality traits of a future engineer, including those that determine his uniqueness in the profession. The most important tasks of professional education are assessing the feasibility of professional activity certain aspects for a student, determining and setting his priorities, and developing his dominant professionally significant qualities. Training a competitive specialist is possible only in a competitive environment. It is proposed to use team management as a mechanism for a competitive environment implementing, and an option for the evaluative-effective component of the education system implementing as an element of this environment is shown. It is noted that the dominant relationships in education can be supplemented by the dominant awareness and relationships in the information space, for example, at the digital educational cluster. The formation of professionally significant qualities in the engineering education system can be allocated into a separate work plan of a unified work upbringing program or of a separate professional training program.